Preparation components and preparation method of ultrathin high-transmittance photovoltaic glass
By using ultra-thin, high-transparent photovoltaic glass preparation components and methods in photovoltaic glass production, using raw materials such as quartz sand, soda ash, limestone and magnetic separation to remove iron, combined with tin tank flow trough and annealing kiln technology, traditional photovoltaics are solved The bubble and iron content problems in the glass improve transparency and optical performance, ensuring the high quality of the photovoltaic glass original sheet.
Patent Information
- Application Number
- CN202411367301.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2024-12-20
AI Technical Summary
In traditional photovoltaic glass production, no special lamination process is formulated for its characteristics, resulting in frequent bubbles, and the iron content in the raw materials affects the color and transparency, resulting in poor quality of the photovoltaic glass raw sheet.
The preparation components and methods of ultra-thin high-transparent photovoltaic glass are adopted, including quartz sand, soda ash, limestone, crushed glass, clarified agent, decolorizer, raw material additive and other raw materials. The iron is removed by crushing and magnetic separation, melting kiln calcination, The tin tank flow trough forms a glass tape and is subjected to a slow cooling in the annealing kiln to reduce the iron content and bubble count.
It significantly reduces the iron content and bubble count of photovoltaic glass, improves transparency and optical properties, and ensures the high light transmittance and quality of the photovoltaic glass original sheet.
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of photovoltaic glass production, and in particular to a preparation component and a preparation method of ultra-thin high-light-transmittance photovoltaic glass. Background Art
[0002] Photovoltaic glass production is mainly divided into two links: raw sheet production and deep processing. In the raw sheet production stage, it mainly includes steps such as batching, melting, clarification, rolling, annealing, slicing and packing. Among them, batching is to accurately weigh and mix various raw materials to form a batch material, and then add a certain amount of broken glass and transport it to the kiln head silo. Melting is to melt, clarify and homogenize the batch material at high temperature to form qualified glass liquid. Clarification is a key step in this process and directly affects the final quality of the glass. The deep processing stage is to further process the raw sheet, including precision cutting, edge grinding, cleaning, coating, tempering, packing and other steps to improve the physical and chemical properties of the glass, and finally obtain the finished product used as the component packaging panel. In the actual production process, it is necessary to strictly control the process parameters and quality standards of each link to ensure that the performance and quality of the final product meet the requirements.
[0003] In the current existing technology, the production of photovoltaic glass sheets requires the steps of batching, melting, rolling, annealing and slicing. Traditional photovoltaic glass has not developed a special lamination process based on its characteristics, which may cause frequent bubbles. In addition, the iron content in the raw materials of photovoltaic glass will affect the color of the photovoltaic glass, and cause the transparency and optical properties to be affected to a certain extent, which in turn leads to poor quality of the produced photovoltaic glass sheets. Therefore, a preparation component and preparation method of ultra-thin and high-transmittance photovoltaic glass are proposed to solve the above problems. Summary of the invention
[0004] 1. Technical issues to be resolved
[0005] In view of the shortcomings of the prior art, the present invention provides a component and method for preparing ultra-thin and highly light-transmittance photovoltaic glass, which has the advantages of few bubbles and low iron content, and solves the problem that traditional photovoltaic glass has no special lamination process formulated according to its characteristics, which may cause frequent bubbles, and the iron content in the raw materials of photovoltaic glass will affect the color of the photovoltaic glass, and cause the transparency and optical properties to be affected to a certain extent, thereby leading to the problem of poor quality of the produced photovoltaic glass sheets.
[0006] (II) Technical solution
[0007] To achieve the above object, the present invention provides the following technical solution: an ultra-thin high-transmittance photovoltaic glass preparation component, comprising the following raw materials: quartz sand, soda ash, limestone, broken glass, clarifier, decolorant, raw material additive, crusher, dryer, conveyor belt, melting furnace, annealing furnace and tin bath
[0008] Preferably, the content of silicon dioxide in the quartz sand is 98-99%, the clarifier is nitrifying salt, the decolorizing agent is manganese dioxide, and the raw material auxiliary agent is potassium oxide.
[0009] Preferably, the quartz sand is 18 parts, the soda ash is 3 parts, the limestone is 8 parts, and the broken glass is 6 parts.
[0010] Preferably, the melting furnace is a smelting furnace, and the annealing furnace is an intermittent gas-fired annealing furnace.
[0011] Another technical problem to be solved by the present invention is to provide a method for preparing ultra-thin high-transmittance photovoltaic glass, comprising the following steps:
[0012] 1) using a pulverizer to grind blocky quartz sand, soda ash, limestone and broken glass respectively, then using a dryer to fully dry the ground limestone to remove moisture, then using a magnetic separation method to remove the iron content in the ground raw materials, controlling the iron content in the ground raw materials to be 0.008-0.012%, and then using a high-precision electronic scale to weigh out 10-16 parts of ground quartz sand, 3-5 parts of ground limestone, 1 part of ground soda ash and 2-4 parts of broken glass;
[0013] 2) The weighed quartz sand, soda ash and limestone are delivered to the melting furnace by means of a conveyor belt, decolorizing agent and raw material additives are added, the temperature in the melting furnace is maintained at 1550-1600°C to continuously heat and calcine the raw materials, and the various raw materials entering the melting furnace are melted and mixed into a liquid state, and then a clarifier is added until the mixed solution is clarified, and then the melting furnace temperature is lowered to control the mixed solution to cool into a glass liquid at 1100-1150°C and form liquid glass, and the liquid glass flows through the flow channel connected to the melting furnace and the tin bath onto the surface of the molten tin liquid, and under the action of the liquid glass's own gravity, surface tension and pulling force, the glass liquid spreads out to form a glass ribbon;
[0014] 3) The glass ribbon is polished and thinned in the tin bath. At this time, the glass ribbon at the end of the tin bath is cooled to 580-620℃. Then the glass ribbon that is about to harden is led out of the tin bath and enters the annealing kiln for heating and annealing using a transition roller. After the glass ribbon is heated to the annealing temperature, it is kept warm and evenly heated to eliminate stress. Then it goes through two stages of slow cooling and rapid cooling to obtain ultra-thin and high-transmittance photovoltaic glass.
[0015] (III) Beneficial effects
[0016] Compared with the prior art, the present invention provides a preparation component and preparation method of ultra-thin high-transmittance photovoltaic glass, which has the following beneficial effects:
[0017] 1. The preparation components and preparation method of the ultra-thin high-transmittance photovoltaic glass, after crushing quartz sand, soda ash and limestone, use magnetic separation to remove iron in the crushed raw materials, thereby greatly reducing the iron content in the crushed raw materials, thereby ensuring the transparency of the crushed raw materials after melting, and then ensuring the transparency and optical properties of the prepared photovoltaic glass, and further improving the transmittance of the photovoltaic glass.
[0018] 2. The preparation components and preparation method of the ultra-thin high-transmittance photovoltaic glass reduce bubbles in the molten glass and remove impurities in the molten glass by adding a decolorizer and a raw material additive before the crushed raw materials are melted, and adding a clarifier after the crushed raw materials are melted. The molten glass flows into the tin liquid surface in the tin tank through a flow channel connected to the tin tank, thereby reducing the generation of bubbles and ensuring the quality of the photovoltaic glass original piece. DETAILED DESCRIPTION
[0019] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0020] Embodiment 1: A preparation component of ultra-thin high-transmittance photovoltaic glass includes the following raw materials: quartz sand, soda ash, limestone, broken glass, clarifier, decolorizer, raw material additive, crusher, dryer, conveyor belt, melting furnace, annealing furnace and tin bath, quartz sand is 18 parts, soda ash is 3 parts, limestone is 8 parts, and broken glass is 6 parts.
[0021] Among them, the content of silicon dioxide in quartz sand is 98-99%, the clarifier is nitrate salt, the decolorizer is manganese dioxide, and the raw material additive is potassium oxide, which can reduce bubbles in the glass liquid and remove impurities in the glass liquid.
[0022] In addition, the melting furnace is a citrus kiln and the annealing furnace is an intermittent gas-fired annealing furnace, thereby ensuring the efficiency of melting raw materials and ensuring the progress of the annealing process.
[0023] A method for preparing ultra-thin high-transmittance photovoltaic glass comprises the following steps:
[0024] 1) using a pulverizer to grind blocky quartz sand, soda ash, limestone and broken glass respectively, then using a dryer to fully dry the ground limestone to remove moisture, then using a magnetic separation method to remove the iron content in the ground raw materials, controlling the iron content in the ground raw materials to be 0.008-0.012%, and then using a high-precision electronic scale to weigh out 10 parts of ground quartz sand, 3 parts of ground limestone, 1 part of ground soda ash and 2 parts of broken glass;
[0025] 2) The weighed quartz sand, soda ash and limestone are delivered to the melting furnace by means of a conveyor belt, decolorizing agent and raw material additives are added, the temperature in the melting furnace is maintained at 1550-1600°C to continuously heat and calcine the raw materials, and the various raw materials entering the melting furnace are melted and mixed into a liquid state, and then a clarifier is added until the mixed solution is clarified, and then the melting furnace temperature is lowered to control the mixed solution to cool into a glass liquid at 1100-1150°C and form liquid glass, and the liquid glass flows through the flow channel connected to the melting furnace and the tin bath onto the surface of the molten tin liquid, and under the action of the liquid glass's own gravity, surface tension and pulling force, the glass liquid spreads out to form a glass ribbon;
[0026] 3) The glass ribbon is polished and thinned in the tin bath. At this time, the glass ribbon at the end of the tin bath is cooled to 580-620℃. Then the glass ribbon that is about to harden is led out of the tin bath and enters the annealing kiln for heating and annealing using a transition roller. After the glass ribbon is heated to the annealing temperature, it is kept warm and evenly heated to eliminate stress. Then it goes through two stages of slow cooling and rapid cooling to obtain ultra-thin and high-transmittance photovoltaic glass.
[0027] Embodiment 2: A method for preparing ultra-thin high-transmittance photovoltaic glass, comprising the following steps:
[0028] 1) using a pulverizer to grind blocky quartz sand, soda ash, limestone and broken glass respectively, then using a dryer to fully dry the ground limestone to remove moisture, then using a magnetic separation method to remove the iron content in the ground raw materials, controlling the iron content in the ground raw materials to be 0.008-0.012%, and then using a high-precision electronic scale to weigh out 12 parts of ground quartz sand, 4 parts of ground limestone, 1 part of ground soda ash and 3 parts of broken glass;
[0029] 2) The weighed quartz sand, soda ash and limestone are delivered to the melting furnace by means of a conveyor belt, decolorizing agent and raw material additives are added, the temperature in the melting furnace is maintained at 1550-1600°C to continuously heat and calcine the raw materials, and the various raw materials entering the melting furnace are melted and mixed into a liquid state, and then a clarifier is added until the mixed solution is clarified, and then the melting furnace temperature is lowered to control the mixed solution to cool into a glass liquid at 1100-1150°C and form liquid glass, and the liquid glass flows through the flow channel connected to the melting furnace and the tin bath onto the surface of the molten tin liquid, and under the action of the liquid glass's own gravity, surface tension and pulling force, the glass liquid spreads out to form a glass ribbon;
[0030] 3) The glass ribbon is polished and thinned in the tin bath. At this time, the glass ribbon at the end of the tin bath is cooled to 580-620℃. Then the glass ribbon that is about to harden is led out of the tin bath and enters the annealing kiln for heating and annealing using a transition roller. After the glass ribbon is heated to the annealing temperature, it is kept warm and evenly heated to eliminate stress. Then it goes through two stages of slow cooling and rapid cooling to obtain ultra-thin and high-transmittance photovoltaic glass.
[0031] Embodiment 3: A method for preparing ultra-thin high-transmittance photovoltaic glass, comprising the following steps:
[0032] 1) using a pulverizer to grind blocky quartz sand, soda ash, limestone and broken glass respectively, then using a dryer to fully dry the ground limestone to remove moisture, then using a magnetic separation method to remove the iron content in the ground raw materials, controlling the iron content in the ground raw materials to be 0.008-0.012%, and then using a high-precision electronic scale to weigh out 16 parts of ground quartz sand, 5 parts of ground limestone, 1 part of ground soda ash and 4 parts of broken glass;
[0033] 2) The weighed quartz sand, soda ash and limestone are delivered to the melting furnace by means of a conveyor belt, decolorizing agent and raw material additives are added, the temperature in the melting furnace is maintained at 1550-1600°C to continuously heat and calcine the raw materials, and the various raw materials entering the melting furnace are melted and mixed into a liquid state, and then a clarifier is added until the mixed solution is clarified, and then the melting furnace temperature is lowered to control the mixed solution to cool into a glass liquid at 1100-1150°C and form liquid glass, and the liquid glass flows through the flow channel connected to the melting furnace and the tin bath onto the surface of the molten tin liquid, and under the action of the liquid glass's own gravity, surface tension and pulling force, the glass liquid spreads out to form a glass ribbon;
[0034] 3) The glass ribbon is polished and thinned in the tin bath. At this time, the glass ribbon at the end of the tin bath is cooled to 580-620℃. Then the glass ribbon that is about to harden is led out of the tin bath and enters the annealing kiln for heating and annealing using a transition roller. After the glass ribbon is heated to the annealing temperature, it is kept warm and evenly heated to eliminate stress. Then it goes through two stages of slow cooling and rapid cooling to obtain ultra-thin and high-transmittance photovoltaic glass.
[0035] The beneficial effects of the present invention are:
[0036] By crushing quartz sand, soda ash and limestone and removing iron from the crushed raw materials by magnetic separation, the iron content in the crushed raw materials is greatly reduced, thereby ensuring the transparency of the crushed raw materials after melting, thereby ensuring the transparency and optical properties of the produced photovoltaic glass, and further improving the light transmittance of the photovoltaic glass. Decolorizers and raw material additives are added before the crushed raw materials are melted, and clarifiers are added after the crushed raw materials are melted to reduce bubbles in the glass liquid and remove impurities in the glass liquid. The glass liquid flows into the tin liquid surface in the tin tank through a flow channel connected to the tin tank, thereby reducing the generation of bubbles and ensuring the quality of the photovoltaic glass original sheet.
[0037] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A preparation component for ultra-thin high-transmittance photovoltaic glass, characterized in that: Includes the following raw materials: quartz sand, soda ash, limestone, broken glass, clarifier, decolorizer, raw material additives, crusher, dryer, conveyor belt, melting furnace, annealing kiln and tin bath.
2. The ultra-thin high-transmittance photovoltaic glass preparation component according to claim 1, characterized in that: The content of silicon dioxide in the quartz sand is 98-99%, the clarifier is nitrifying salt, the decolorizing agent is manganese dioxide, and the raw material auxiliary agent is potassium oxide.
3. The ultra-thin high-transmittance photovoltaic glass preparation component according to claim 1, characterized in that: The quartz sand is 18 parts, the soda ash is 3 parts, the limestone is 8 parts, and the broken glass is 6 parts.
4. The ultra-thin high-transmittance photovoltaic glass preparation component according to claim 1, characterized in that: The melting furnace is a citrus furnace, and the annealing furnace is an intermittent gas-fired annealing furnace.
5. A method for preparing ultra-thin high-transmittance photovoltaic glass, characterized in that: The following steps are involved: 1) using a pulverizer to grind blocky quartz sand, soda ash, limestone and broken glass respectively, then using a dryer to fully dry the ground limestone to remove moisture, then using a magnetic separation method to remove the iron content in the ground raw materials, controlling the iron content in the ground raw materials to be 0.008-0.012%, and then using a high-precision electronic scale to weigh out 10-16 parts of ground quartz sand, 3-5 parts of ground limestone, 1 part of ground soda ash and 2-4 parts of broken glass; 2) The weighed quartz sand, soda ash and limestone are delivered to the melting furnace by means of a conveyor belt, decolorizing agent and raw material additives are added, the temperature in the melting furnace is maintained at 1550-1600°C to continuously heat and calcine the raw materials, and the various raw materials entering the melting furnace are melted and mixed into a liquid state, and then a clarifier is added until the mixed solution is clarified, and then the melting furnace temperature is lowered to control the mixed solution to cool into a glass liquid at 1100-1150°C and form liquid glass, and the liquid glass flows through the flow channel connected to the melting furnace and the tin bath onto the surface of the molten tin liquid, and under the action of the liquid glass's own gravity, surface tension and pulling force, the glass liquid spreads out to form a glass ribbon; 3) The glass ribbon is polished and thinned in the tin bath. At this time, the glass ribbon at the end of the tin bath is cooled to 580-620℃. Then the glass ribbon that is about to harden is led out of the tin bath and enters the annealing kiln for heating and annealing using a transition roller. After the glass ribbon is heated to the annealing temperature, it is kept warm and evenly heated to eliminate stress. Then it goes through two stages of slow cooling and rapid cooling to obtain ultra-thin and high-transmittance photovoltaic glass.
